Financial solutions for small and medium enterprises: Improving technology level and marketing strategy - Hung, Tran Huy; Anh, Pham Hoang; Dang, Pham Van; Luyen, Le Van (Edelweiss Applied Science and Technology, 2025)
It clarifies the conceptual elements of technology level, marketing strategy, and SMEs’ business performance based on the theoretical framework. In addition, this study looked at how SMEs’ business performance is affected by their amount of technology and marketing strategy. The objective of this study is to quantify and examine the impact of technological proficiency and marketing strategy on the operations of small and medium-sized businesses (SMEs) in the province of Thai Binh. By examining the contents of the technology level, marketing strategy, and business performance, the inductive technique was used to define the study problem. Both qualitative and quantitative research methodologies are employed. While the quantitative research approach uses primary data gathered through a survey, the qualitative research method uses the interview methodology. A total of 245 survey forms from SMEs in the province of Thai Binh make up the sample size. The survey was carried out between August and November of 2024. The impact of technology level and marketing strategy on SMEs’ business performance was measured and examined using SPSS. For data analysis, a variety of statistical methods were used, such as descriptive statistics in SPSS, Cronbach’s alpha coefficient for scale reliability analysis, EFA analysis, correlation analysis, and regression model. According to the study’s findings, SMEs have an average level of technology and marketing strategy, which impacts their business performance, with the level of technology having a stronger influence. This study provides both theoretical and practical implications for raising technology levels as a cost-effective way to boost company performance. The paper makes some suggestions for SMEs in light of this finding.